Analysis of Grammatical Errors in Arabic Speech Texts at the Padang Pasir Festival, UIN Walisongo Semarang - Khoirunnisah Harahap (CV Edukastra Mandiri, 2025)
Speech as a form of oral communication requires careful preparation, especially in the preparation of a script that is in accordance with the rules of Arabic grammar. For this reason, research on grammatical error analysis needs to be carried out, in order to examine language errors that often appear in Arabic speech texts, especially nahwu and sharaf errors that affect audience understanding and the effectiveness of message delivery. In order to achieve this goal, the researcher as the main instrument carried out in-depth observations of 15 Arabic speech texts at the Padang Pasir Festival of UIN Walisongo Semarang. This research uses a qualitative approach. The methods used to collect data are observation and documentation. While in analyzing the data, Tarigan's method (1990) is used which includes 5 steps; collecting error samples, identifying errors, explaining errors, classifying errors, and evaluating errors. The results of this study showed that grammatical errors in writing Arabic speech texts were categorized into several aspects, namely inconsistencies between tadzkir and ta'nis, na'at errors against man'ut, Sharaf errors, idhafah errors, adad and ma'dud errors and I'rab errors. The main causative factors are the lack of mastery of grammar, the influence of the first language, the limited Arabic vocabulary, and the lack of habit of reading Arabic literature.